2003
DOI: 10.1519/1533-4287(2003)017<0095:eodsco>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Set Configurations on Barbell Velocity and Displacement During a Clean Pull

Abstract: The effects of 3 types of set configurations (cluster, traditional, and undulating) on barbell kinematics were investigated in the present study. Thirteen men (track and field = 8; Olympic weightlifters = 5) (mean +/- SEM age, 23.4 +/- 1.1 years; height, 181.3 +/- 2.1 cm; body mass, 89.8 +/- 4.2 kg) performed 1 set of 5 repetitions in a cluster, traditional, and undulating fashion at 90 and 120% of their 1 repetition maximum (1RM) power clean (119.0 +/- 4.3 kg). All data were collected at 50 Hz and analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(115 citation statements)
references
References 0 publications
6
98
2
1
Order By: Relevance
“…Recognizing that fatigue can result from a decrease in a muscle's force generating capacity or contraction velocity, the definition of fatigue includes a decrease in the expected or required power output (Fitts 1994). While the causes of fatigue are not fully understood (Fitts 1994), the original CLU model by Haff et al (2003) was based upon the assumption that short intra-set rest periods would provide sufficient time for partial replenishment of PCr allowing for the ability to produce greater power in subsequent repetitions. In support, Gorostiaga et al (Gorostiago 2012) reported a near-complete depletion of PCr stores when performing leg press using TRD and suggested increases in lactate and byproducts of metabolism may contribute to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that fatigue can result from a decrease in a muscle's force generating capacity or contraction velocity, the definition of fatigue includes a decrease in the expected or required power output (Fitts 1994). While the causes of fatigue are not fully understood (Fitts 1994), the original CLU model by Haff et al (2003) was based upon the assumption that short intra-set rest periods would provide sufficient time for partial replenishment of PCr allowing for the ability to produce greater power in subsequent repetitions. In support, Gorostiaga et al (Gorostiago 2012) reported a near-complete depletion of PCr stores when performing leg press using TRD and suggested increases in lactate and byproducts of metabolism may contribute to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Although neither study analyzed RPE during their investigation, it can be speculated that IRR may manifest changes to RPE due to attenuation of fatigue. If fatigue decreases power output and is an unwanted byproduct during power training, based on the previous findings (Singh et al 2007;Haff et al 2003;Lawton et al 2006), IRR may be a rational methodology to attenuate increases in RPE when training for power. Interestingly, the effects of IRR on RPE are still unknown, but there seems to be an association between RPE, fatigue, and power output.…”
Section: Introductionmentioning
confidence: 93%
“…This method of training employs taking brief periods of rest (15-45 s) between repetitions (Haff et al 2003;Lawton et al 2006), and two studies have examined their effect on resistance training performance. Haff et al (2003) and Lawton et al (2006) demonstrated IRR to attenuate fatigue, which allowed for the maintenance of power, velocity, and displacement during a single set exercise protocol.…”
Section: Introductionmentioning
confidence: 99%
“…This statement ultimately leads to the question: Can the explosive triple extension movement be trained with weightlifting pulling derivatives that do not require the catch phase? Recent literature reflects researchers' interest in this question, as a number of studies have examined several clean and snatch pulling derivatives, including the clean pull [66], snatch pull [118,129], hang high pull [68,69,119], jump shrug [64,69,70], and mid-thigh pull [2,25,26,65,67], discussed their technique [60][61][62][63], and discussed their implementation in resistance training programs [54]. It should be noted that each of the previous pulling derivatives could be used as part of the teaching progression for the full weightlifting movements [60][61][62][63]69].…”
Section: Weightlifting Pulling Derivativesmentioning
confidence: 99%
“…However, this does not mean that athletes cannot benefit from using weightlifting pulling derivatives that remove the catch phase and emphasize the completion of the explosive triple extension movement [54,56,59]. In this light, researchers have discussed the technique of weightlifting pulling derivatives [60][61][62][63] as well as examined their kinetic and kinematic potential as training exercises [2,[64][65][66][67][68]. Furthermore, weightlifting pulling derivatives have been compared with full weightlifting movements to determine which exercises may produce a superior training stimulus [25,26,69,70].…”
mentioning
confidence: 99%